The Renminbi and Poor-country Growth - Chris Garroway; Burcu Hacibedel; Helmut Reisen; Edouard Turkisch (The World Economy, 2012)
The paper estimates i) the degree of currency undervaluation and its relationship with per capita income (convergence), as informed by the Harrod-Balassa-Samuelson (HBS) framework. ii) The role of the real effective exchange rate, both its level and its stability over time, for underpinning growth in developing countries, especially in large dual economies such as China and India. iii) New empirical evidence on growth linkages between China and poor countries for the last two decades and on potential displacement effects of renminbi (RMB) appreciation.
Keywords: F15; F31; 330; Renminbi; China impact; Integration; Wechselkurs